THE ROLE OF ESP IN INTERNATIONAL BUSINESS AND NEGOTIATIONS THE CONTRIBUTION OF PRIVATE UNIVERSITIES - Shahrabonu Qurbonova; Maftuna Nurova (TADQIQOTLAR, 2025)
Annotation: This article discusses the changing role of internet shopping in modern consumer trends and business practice. It analyzes the advantages and disadvantages of e-commerce, its effect on traditional retailing, and the technology developments behind this shift. The article provides solutions to problems and tips for safe and effective online shopping